Recent Study of Coccidiosis in Broiler Closed House: The Role of Some Aspects of Maintenance - Endro Yuwono; Reka Putra Wandatara; Sri Mastuti; Diana Indrasanti (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
This study aimed to determine the role of different factors in raising broiler chickens in closed-house cages that affect the increased cases of coccidiosis in partnership farms. These factors are cage management, the level of cage cleanliness, the chicken-rearing period, and the prevalence of coccidiosis in partnership farms. The research was conducted from May to December 2022 in 11 closed-house broiler farms in the Kalibagor Subdistrict, Banyumas Regency. This study applied survey method and a purposive sampling, and determined the sample size by the Slovin formula, collecting 100 samples in total. The materials were broiler chicken feces collected in the initial and final phases, and data on maintenance management were collected using a questionnaire. Data were subjected to descriptive analysis and Chi-square calculations. The results stated that the prevalence of coccidiosis in Kalibagor Subdistrict was 29%, and coccidiosis occurrence at the starter and finisher periods was 6% and 52%, respectively. The results of the Chi-square analysis show a significant difference in coccidiosis occurrence among broiler rearing periods. The effect of the level of cleanliness is also significant in the occurrence of coccidiosis in Kalibagor Subdistrict, Banyumas Regency. This study concludes that the occurrence of coccidiosis in closed-house broiler chickens on partnership farms is quite low, and the level of cleanliness and rearing period is very influential on the occurrence of coccidiosis.